2021
DOI: 10.21203/rs.3.rs-317281/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A quantitative description of the spatial-temporal distribution and evolution pattern of world cultural heritage

Abstract: Depicting the temporal and spatial evolution pattern of global world cultural heritage systematically and finely is the basis of heritage recognition and protection. In this study, 869 world cultural heritage inscriptions (through 2019) were selected as the research objects, and the times and types of each World Heritage site were manually annotated from more than 5000 pieces of data. Through time series modelling, the advantages of and changes in heritage declarations in different regions and periods were ana… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
(17 reference statements)
0
5
0
Order By: Relevance
“…Cultural heritage sites are primarily distributed across the Song and Yuan Dynasties and the Ming and Qing Dynasties, and those from the Ming and Qing Dynasties are the most prominent. The cultural heritage sites of the Yellow River Basin are different across the historical periods, but they are relatively concentrated in their respective distribution areas of the era, and their overall trend rebounds in the historical period [ 25 31 ]. Along the spatial dimension, the cultural heritage sites of the Yellow River Basin are characterized by large agglomeration and small dispersion.…”
Section: Temporal and Spatial Characteristics Of Cultural Heritage By...mentioning
confidence: 99%
“…Cultural heritage sites are primarily distributed across the Song and Yuan Dynasties and the Ming and Qing Dynasties, and those from the Ming and Qing Dynasties are the most prominent. The cultural heritage sites of the Yellow River Basin are different across the historical periods, but they are relatively concentrated in their respective distribution areas of the era, and their overall trend rebounds in the historical period [ 25 31 ]. Along the spatial dimension, the cultural heritage sites of the Yellow River Basin are characterized by large agglomeration and small dispersion.…”
Section: Temporal and Spatial Characteristics Of Cultural Heritage By...mentioning
confidence: 99%
“…At present, some studies have examined cultural heritage [42][43][44] and intangible cultural heritage based on the spatial analysis and influencing factors of geographic information systems (GISs) [45]. In a study by Yao et al [42], 81.9% of Christian cultural heritage was concentrated in Europe.…”
Section: Introductionmentioning
confidence: 99%
“…In a study by Yao et al [42], 81.9% of Christian cultural heritage was concentrated in Europe. Liang et al [43] concluded that the number of cultural heritage sites is much higher in Europe and North America than in Asia and the Pacific. Heritage sites are affected by many factors, such as global political, political and economic crises.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, to protect the space, it is first necessary to clarify the relationship between spatial transition and the social factors (Institutional, departmental, and social environment) behind it (Elizabeth, & Lesley, 2010). For this reason, it is necessary to clarify the evolution of the distribution of cultural heritage scattered throughout the region and its social and cultural context to protect and create character and preserve and utilize architecture in the region (Liang, Yang, Wang, Yang, & Chen, 2021;Li et al, 2021). In addition, this will allow us to embody a unique tourist culture that will lead to the formation of sustainable tourist destinations in the future (Japan Travel Bureau, 2013).…”
Section: Introductionmentioning
confidence: 99%